Determining Frailty in People With Intellectual Disabilities in the COVID‐19 Pandemic - Festen, Dederieke A. M. (J Policy Pract Intellect Disabil, 2021)
BACKGROUND: Across the world, frailty is part of the guidelines that are being developed in the COVID‐19 pandemic for triaging in crisis situations. The Clinical Frailty Scale (CFS) evaluates the ability to perform daily tasks to identify frail individuals, potentially excluding those from intensive care (IC) treatment. Individuals with intellectual disabilities (ID) experience varying degrees of dependence, distinct from age‐related physical deterioration. Using the CFS for triage in crisis situations could potentially unjustifiably exclude individuals with ID from IC treatment. Our objective was to compare the classification of individuals with ID into different frailty categories based on the CFS and the well‐studied ID‐frailty index and to determine suitability of CFS for evaluation of frailty in individuals with ID during the COVID‐19 pandemic. METHODS: This retrospective analysis of the observational healthy aging and intellectual disabilities (HA‐ID) study included 982 individuals with ID of ≥50 years, who were classified according to the CFS and the ID‐frailty index. RESULTS: Of the cohort of 982 older adults with ID, 626 (63.7%) would be classified as moderately frail (CFS score 6), but 92% of this group is not moderately frail according to the ID‐frailty index. Furthermore, 199 (20.3%) would be classified as at least severely frail (CFS score 7–9), but 74.9% of this group is not severely frail according to the ID‐frailty index. Overall, 730 out of 982 (74.9%) individuals would be incorrectly classified by the CFS as too frail to have a good probability of survival. The ID‐frailty index predicts mortality better than the CFS in individuals with ID. CONCLUSIONS: Our results show the CFS is not suitable to evaluate frailty in individuals with ID, with potential dramatic consequences for triage and decision‐making during the COVID‐19 pandemic. We strongly recommend using the ID‐frailty index when assessing probability of survival for individuals with ID.